ESTRÉS DURANTE LA PANDEMIA EN ENFERMEROS QUE LABORAN PRIMERA LÍNEA EN UN HOSPITAL COVID-19 EN LIMA - Aldazabal Puma, Yaqueline (2020)
Objectives: This study sought to determine stress during the pandemic in nurses who work first line in a COVID-19 hospital in Lima. Materials and methods: The focus of the study was quantitative, in terms of the design used it was descriptive-transectional. The population consisted of 102 nurses who work on the front line. The survey technique was used and the main variable was measured with the Nurse Stress Scale (NSS), which allows measuring the level of stress in nursing professionals. This measurement instrument is composed of 34 items and 3 dimensions. Results: In relation to sex, 84 were men (82.2%) and 18 were women (17.6%). Regarding stress in nurses, the low level predominated with 47.1% (n = 48), followed by the medium level in 42.2% (n = 43) and the high level with 10.8% (n = 11). Regarding its dimensions, in the physical environment the low level predominated with 57.8% (n = 59), followed by the medium level in 36.3% (n = 37) and the high level with 5.9% (n = 6 ); in the psychological environment, the medium level predominated with 47.1% (n = 48), followed by the low level in 42.2% (n = 43) and the high level with 10.8% (n = 11); in the social environment the low level predominated with 55.9% (n = 57), followed by the medium level in 34.3% (n = 35) and high with 9.8% (n = 10). Conclusions: According to stress in nurses, the low level predominated; Regarding its dimensions, in physical environment and social environment the low level prevailed and in psychological environment the medium level.